Non-invasive brain stimulation in cognitive sciences and Alzheimer's disease - Claudia Carrarini; Chiara Pappalettera; Chiara Pappalettera; Domenica Le Pera; Paolo Maria Rossini (Frontiers in Human Neuroscience)
Over the last four decades, non-invasive brain stimulation techniques (NIBS) have significantly gained interest in the fields of cognitive sciences and dementia care, including neurorehabilitation, for its emerging potential in increasing the insights over brain functions and in boosting residual cognitive functions. In the present paper, basic physiological and technical mechanisms and different applications of NIBS were reviewed and discussed to highlight the importance of NIBS in multidisciplinary and translational approaches in clinical and research settings of cognitive sciences and neurodegenerative diseases, especially in Alzheimer's disease. Indeed, NIBS strategies may represent a promising opportunity to increase the potential of neuromodulation as efficacious interventions for individualized patients care.